Strategi Manajemen Masjid Dalam Meningkatkan Kenyamanan Jamaah Pada Masjid Al Azhar Center Parepare - Iskandar Iskandar (Jurnal Kajian Manajemen Dakwah, 2021)
This study discusses the management strategy of the Al Azhar Islamic Centre Parepare mosque. The purpose of this study was to determine the implementation of mosque management strategies at the Al Azhar Islamic Centre Parepare mosque and to determine the supporting and inhibiting factors in increasing the comfort of worshipers at the Al Azhar Islamic Centre Parepare mosque. This type of research uses a qualitative approach in collecting data using the methods of observation, interviews and documentation. The data sources are from mosque administrators and mosque congregations. The data analysis technique used is data reduction, data presentation and conclusion drawing. The theory used is strategic management theory and SWOT analysis theory. The results showed that the management of the Al Azhar Islami Centre Parepare mosque implemented a management strategy through the stages, namely (1) environmental analysis, strategy formulation, strategy implementation and strategy evaluation which were very helpful in implementing management strategies at the Al Azhar Islamic Centre mosque. (2) the supporting factors that occur at the Al Azhar Islamic Centre Parepare mosque are good management cooperation and communication, the support from the congregation and also supported by an adequate financial budget. Meanwhile, the inhibiting factor is the improvement of mosque facilities, namely the wudhu and mosque toilets which have not yet been realized and other obstacles are also regarding the safety of the mosque.